Prevalence and detection of counterfeit pharmaceuticals: A mini review - Fernandez, F; Green, MD; Newton, P (2008)
Counterfeit drugs are a widespread, important public health problem. This mini review reports on the current status of the issue of drug counterfeiting, with special emphasis on our findings on counterfeit anti-infectives, and the new detection tools being developed to identify and characterize fake drugs. © 2008 American Chemical Society.